A Review of Legal Protection for Minors Against Sexual Violence (Case Study in Bekasi City) - Yuka Dinda Permata; Faisal Santiago (Al-Makki Publisher, 2026)
Crimes of sexual violence against minors are a serious problem that requires special attention from a legal perspective. Children, as a vulnerable group, have the right to protection from all forms of violence, including sexual violence, which can have profound impacts on their physical, psychological, and social development. This study aims to analyze the legal framework for the protection of minors who are either victims or perpetrators of sexual violence, as well as to assess the effectiveness of the implementation of applicable laws and regulations. The method employed in this study is a normative juridical approach, examining laws and regulations, legal literature, and relevant court decisions. The results indicate that while legal protection for children is provided under various regulations, practical challenges remain. These include weak law enforcement, limited rehabilitation support for victims, and inadequate coordination among relevant stakeholders. Therefore, synergy between law enforcement agencies, government institutions, and the community is essential to improve legal protection for minors against sexual violence. Preventive and educational measures, combined with firm and just law enforcement, are crucial in addressing this problem effectively and ensuring the safety and well-being of children.